Em busca da essência do self: um espetáculo da vivência de estudos de professores no exterior sob a perspectiva da complexidade - Aires, Daniela Santos (2014)
This reasearch aims to present the performance of investigation of the phenomenon the identíty construction of foreign /anguage teachers from their studying experience abroad, in order to offer a knowledge base which may contribute to a deeper understanding of how foreign language teachers construct their identity and how they deal with identity features, which can be important both for the formation of future teachers, as for the preparation of new exchange students, which are issues of social relevance. The repertoire defined to theoretically support this research is based on complexity (Morin, 2007, 2008; Morin; Le Moigne, 2000), which assumes the non-fragmented, non-reducionist, non-linear, dialogic, recursive and hologramatic traits of human relations and experiences which are interconnected and integrated with an alive, dynamic and systemic reality. This study is also carried out and articulated with identity and identity construction concepts on their linguistic and emocional aspects (Norton, ;. 1997; Revuz, 1998/2006; Duff; Uchida, 1997; Hall, 2003; Moita Lopes; Bastos, " 2010; Pennycook, 2006, 2011; Rajagopalan, 2003, 2004, 2006; Signorini, 1998, 1998a, 2006; Pavlenko, 2002). Metodologically, the show is organized based on the hermeneutic-phenomenological approach (van Manen, 1990; F eire, 1998, 2010, 2012, 2012a), a qualitative methodological orientation which focuses on describing and interpreting phenomena of human experience: ilfl order to investigate their essence and which may establish an interesting dialogue with the principies of complexity. The research participants were three teachers: twa of them were English teachers (although one of them gave up the study before concluding the investigation), and one French teacher. To achieve its objectives, the curriculum vitae, narratives and the hermeneutic conversations were used as instruments for gathering texts. The nature of the collected material enabled itto be refined and reframed until hermeneutic-phenomenological themes were found: search, immersion, be/onging and self-know/edge which are related to dreqm, improvement, opportunity, credibility, fluency, findings, necessity, adaptapil!ty, readaptability and autonomy - which are also described and interpreted in this study as subthemes